Prevalence and associated factors of mental distress among private college nursing students in Gondar town, Northwest Ethiopia, 2023 - Amare, Agegnehu; Ygzaw, Ngusie; Tesfaye, Bizuneh; Trfeneh, Ennguday; Tinsae, Seblewengel; Temesgen, Kiber; Mesafint, Gebremeskel (Frontiers in Psychiatry, 2025)
BackgroundMental distress (MD) refers to a range of troubling, confusing, or unusual internal experiences and symptoms that affect more than 25% of people during their lives. Students with mental distress are more likely to face negative outcomes, including impaired cognitive functioning, learning difficulties, poor academic performance, and substance use. This study aimed to address a research gap by estimating the prevalence of mental distress and identifying associated factors.MethodsAn institution-based cross-sectional study was conducted in Gondar town using a multistage stratified sampling technique. The Kessler 10-item scale was applied to assess the prevalence of mental distress. Bi-variable and multivariable logistic regression analyses were performed, and variables with a p-value <0.05 in the multivariable model at a 95% confidence interval (CI) were considered statistically significant.ResultsThe prevalence of mental distress among private college nursing students was 52.7% (95% CI: 48.8%–56.7%). In the multivariable analysis, factors significantly associated with mental distress were female sex (AOR = 2.8, 95% CI: 1.50–3.16), rural residence (AOR = 1.96, 95% CI: 1.30–2.95), poor social support (AOR = 2.03, 95% CI: 1.20–3.42), not participating in regular physical exercise (AOR = 3.28, 95% CI: 1.68–6.37), never attending guidance and counseling services (AOR = 2.37, 95% CI: 1.12–4.99), and a family history of mental illness (AOR = 2.65, 95% CI: 1.31–5.35).Conclusion and recommendationsThe prevalence of mental distress was notably high. Associated factors included sex, residence, social support, physical exercise, access to guidance and counseling services, and family history of mental illness. We recommend that the Ministry of Health and Ministry of Education strengthen guidance and counseling services and promote regular physical exercise at the college level.